Midterm Follow‐up After Retrievable Inferior Vena Cava Filter Placement in Venous Thromboembolism Patients With or Without Malignancy. Issue 4 (6th March 2015) - Myojo, Masahiro; Takahashi, Masao; Tanaka, Tomofumi; Higashikuni, Yasutomi; Kiyosue, Arihiro; Ando, Jiro; Fujita, Hideo; Komuro, Issei; Hirata, Yasunobu
Abstract Background A clear indication and strategy for placement of retrievable inferior vena cava filters (IVCFs) have not been established. This study was designed to evaluate the efficacy and disadvantages of the retrievable IVCF use particularly in venous thromboembolism (VTE) patients with malignancy. Hypothesis Retrievable IVCFs might be safe and useful in VTE patients with malignancy. Methods The study population consisted of 56 consecutive patients undergoing IVCF placement at our institution from January 1, 2008 to December 31, 2011. Prognostic data were retrospectively reviewed in April 2013. Results Mean follow‐up period was 584.6 (range, 1–1857) days. Twenty‐six of the 56 patients had a malignancy. In 16 of the 30 patients without malignancy, the filter was retrieved, whereas the other 14 patients eventually received permanent implantation. There was no significant difference in the survival rate between the retrieval group and the nonretrieval group in the nonmalignancy patients (1‐year survival rates, 94% vs 85%). In patients with malignancy, the nonretrieval group showed a significantly lower survival rate (P < 0.01). The 1‐year and 2‐year survival rates were 100% vs 46% and 100% vs 18%, respectively. There was no medical record of pulmonary thromboembolism occurrence or recurrence. All deaths in the patients with malignancy were malignancy related. In 4 of 5 malignancy patients who could undergo tumor resection surgery, adequate thrombus regression enabled us to retrieve the IVCF after surgery. Conclusions Permanent use of a retrievable IVCF is relatively safe in short‐ or midterm follow‐up regardless of malignancy status. Retrievable filter use might be reasonable in malignancy patients.